Caracterización de las áreas urbanas gallegas en función de los flujos de movilidad obligada - José Antonio Aldrey Vázquez; Miguel Pazos Otón; Román Rodríguez González; Jorge Vicente Díaz (Cuadernos de Geografía de la Universitat de València)
Territorial reality in Galician municipalities evolved to different rhythms, affected by very different dynamics in each one of the cases. The problems in the application of the town-planning and technical instruments for land management provoked the disconnection between cities and their metropolitan nature. Areas of influence in Galician cities present complex models, adapted to the difficulties which deprived them from a prudent and coherent management of the new urban territories. In the assessment of the new urban reality, its conditions and characteristics, residential mobility is a key issue of analysis. The scale of the process of urbanization is a result of these behaviours with regard to mobility. In fact, mobility has intensified in the last years and clearly shows real functional dynamics, needing a new and urgent territorial organization and governance.